GADHON SALIN SWARA: INTERPRETASI GAMELAN GADHON - Laurentius Hanan; Wahyu Thoyyib Pambayun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This article recounts the author's experience in the process of composing "Gadhon Salin Swara." The composition is inspired by the gadhon gamelan. Drawing from the gadhon gamelan, the author is motivated to interpret rhythmic patterns that encompass cengkok, sekaran, gerongan, balungan, and the relationships between instruments. The stages of composition include orientation, observation, exploration, composition, and evaluation. Through this process, the author generates new approaches to approaching instrument crafting, particularly within the context of the gadhon gamelan. The author's approach involves developing patterns, maximizing traditional techniques to create dynamics in the composition, and fostering connections between instruments. It is expected that this article will be useful in understanding the author's creative process in composing "Gadhon Salin Swara."